Repercussions in the effect of echoic prompts, motivating operations on manding on a child with autism and paintings in their steps fractals (2015)
ABSTRACT: For children with autism, manding is useful for teaching new forms of behavior. A multiple baseline design consisted of one stimulus class of manding opportunity that the experimenter classified into three response classes (libro, cookie, and bola). A functional relationship between high levels of independent manding and the onset of the echoic prompts and EO manipulations was replicated across three different mands. The pattern of responding across the three vocal behaviors emitted by the participant verified the behavior change. The present study would enhance the results of Hall and Sundberg (1987) while manipulating the presence of EOs during mand-echoic training. A limitation to the current study that warranted discussion was that because only one participant was included, replication of theses procedures with other participants was needed. The results of this study were socially significant.